Leveraging Digital Transformation for Green Competitive Advantage: Synergistic Role of Circular Economy Practices and Environmental Performance - Younis, Nimra; Ejaz, Faisal; Jagirani, Tahir Saeed; Alwadi, Belal Mahmoud; Ejaz, Sarmad; Hossain, Md Billal (International Journal of Energy Economics and Policy, 2025)
The purpose of the present study is to examine how digital transformation influences the circular economy practices and environmental performance of SMEs so that they can achieve a green competitive advantage. The present study poses the following question of research: i) What is the influence of digital transformation on green competitive advantage? ii) Do circular economy practices and environmental performance mediate the influence of digital transformation on green competitive advantage? The research retrieves theoretical support from the Practice-Based View. The quantitative method was employed to test the model, and data were collected using a survey questionnaire from SMEs in Lahore. 350 questionnaires were distributed to the employees of SMEs using the convenience sampling technique, and 293 questionnaires were returned and filled. The data was analyzed using SPSS and PLS-SEM. The research study's findings indicated that digital transformation is positively linked with the green competitive advantage of SMEs. The results also highlighted that digital transformation significantly influences circular economy practices and environmental performance. The study's outcomes also showed that circular economic practices and environmental performance mediate the direct relationship between digital transformation and green competitive advantage. The intermediary role of circular economy practices and environmental performance in connecting digital transformation and green competitive advantage is substantial. SMEs can improve the efficiency of resources, reduce wastage, and adopt sustainable practices and models through the integration of digital technologies that ultimately enhance environmental performance. The study offers useful insight into policy implications, underscoring the prerequisite for government support, economic spurs, and governing frameworks for encouraging the adoption of digital technologies to achieve sustainability. The policymakers should expedite access to digital tools, endorse ecological revolution, and create an environment that nurtures circular economy practices, allowing SMEs to achieve competitive advantage, along with fostering sustainability.